Interface stress in socket/residual limb with transtibial prosthetic suspension systems during locomotion on slopes and stairs - Eshraghi, A.; Abu Osman, Noor Azuan; Gholizadeh, H.; Ali, S.; Wan Abas, Wan Abu Bakar (2015)
OBJECTIVE: This study aimed to compare the effects of different suspension methods on the interface stress inside the prosthetic sockets of transtibial amputees when negotiating ramps and stairs. DESIGN: Three transtibial prostheses, with a pin/lock system, a Seal-In system, and a magnetic suspension system, were created for the participants in a prospective study. Interface stress was measured as the peak pressure by using the F-socket transducers during stairs and ramp negotiation. RESULTS: Twelve individuals with transtibial amputation managed to complete the experiments. During the stair ascent and descent, the greatest peak pressure was observed in the prosthesis with the Seal-In system. The magnetic prosthetic suspension system caused significantly different peak pressure at the anterior proximal region compared with the pin/lock (P = 0.022) and Seal-In (P = 0.001) during the stair ascent. It was also observed during the stair descent and ramp negotiation. CONCLUSIONS: The prostheses exhibited varying pressure profiles during the stair and ramp ascent. The prostheses with the pin/lock and magnetic suspension systems exhibited lower peak pressures compared with the Seal-In system. The intrasystem pressure distribution at the anterior and posterior regions of the residual limb was fairly homogenous during the stair and ramp ascent and descent. Nevertheless, the intrasystem pressure mapping revealed a significant difference among the suspension types, particularly at the anterior and posterior sensor sites.